Does structural change boost the energy demand in a fossil fuel-driven economy? New evidence from Iran. (1st September 2022) - Oryani, Bahareh; Kamyab, Hesam; Mоridiаn, Аli; Azizi, Zahra; Rezania, Shahabaldin; Chelliapan, Shreeshivadasan
Abstract: Based on data availability, this study investigates the impact of structural change on energy consumption (EC) in Iran from 1976 to 2017. Therefore, the economic complexity index (ECI) was incorporated into the energy demand besides real GDP (RGDP) and real energy price index (REPI), which is constructed based on Iran's leading energy carriers. Multiple econometrics techniques are applied to deliver a more reliable and accurate analysis, such as the autoregressive distributed lag model, error correction model, Bayer and Hanck cointegration test, and three cointegration regressions: fully-modified ordinary least square (OLS), dynamic OLS, and canonical cointegrating regression, and finally Breitung-Candelon Spectral Granger. In the short and long-run, RGDP and ECI increase (rebound effect) EC while REPI reduces it. Furthermore, the causality results show that RGDP, ECI, and REPI are linked to EC in the short, medium, and long run. The study's results have implications for policymakers to manage Iran's energy consumption. They highlighted the importance of raising public environmental awareness, diversifying the energy mix, and continuing to implement the law on targeted subsidy. Highlights: The impact of the structural change on energy demand in Iran was investigated. The ARDL, ECM, Byer and Hank, Breitung-Candelon Spectral Granger were conducted. The robustness was checked by applying FMOLS, DOLS, and CCR. The economic complexity index and the eoncomic growth are positively linked to energy consumption. Energy price is reversely linked to energy demand.